Splitting failure of reinforced concrete columns - Pham, Thanh Phuong (2013)
Many earthquake reconnaissance studies have revealed a unique splitting failure mode of RC columns that has yet to be fully elucidated. Most available shear strength models in the current codes are established based on the concept of a diagonal shear plane in which shear force must be transferred through; this concept might not be as applicable to RC columns failed by vertical cracks, or splitting failure under an earthquake action. In this study an alternative load-transferring path is proposed which not only explains the failure mechanism but also allows for the estimation of shear strength of the test specimens. Experimental observations from seventeen RC columns which underwent splitting failure were used to validate the proposed model. To enhance the applicability of the model, it was further corroborated with 89 short columns screened from existing literature. The validations showed that, while simple to apply, the proposed model can give better predictions of shear strength for RC short columns than other shear strength models available in literature.